WUJUD BANGGA TERHADAP BAHASA DAN SASTRA INDONESIA MENEROKO KEGIATAN SABDA SASTRA - Ramadan, Rafli Rifqi (Universitas Tanjungpura, 2023)
ABSTRACTSabda Literature 22 is a series of language months in commemoration of the National Language Day which was held at Sman 22 Bandung City. The purpose of this literary saying is to improve literacy as well as learning language and literature in the Sman 22 Bandung environment, so that students can get to know and understand Indonesian language and literature in a more interesting way. However, in reality there are still some students who think that this is underestimated and not given much attention resulting in a low quality of literacy, therefore to improve it this literary saying 22 activity is held. The aims of this research are 1. To describe what activities take place in this language month, 2. What lessons are contained in this 22 literary saying, and 3. The impact of this activity. With a qualitative descriptive research method, it is hoped that it will be able to explore the activities studied thoroughly and obtain results that emphasize meaning rather than generalizations. The results of this article are that learning language and literature can be done in various ways so that the delivery can be understood by students and packaged in a different and interesting way.